Total Hip Replacement Using Imageless Computer Navigation for Femoral Neck Fracture in Elderly Patients - Sueajui, MD, Jithayut; Suksathien, MD, Yingyong (Journal of Southeast Asian Orthopaedics, 2022)
Purpose: To determine the incidence of dislocation after total hip replacement (THR) using imageless computer navigation in older adults with femoral neck fractures. Methods: A retrospective review of femoral neck fractures in older adults who underwent THR with imageless computer navigation between January 2018 and December 2019 was performed. We evaluated the dislocation rate as the primary outcome measure. Furthermore, we evaluated the acetabular component position using computed tomography, functional outcome using the Barthel index score, and perioperative complications as secondary outcomes. Results: Of the 50 patients who underwent THR, no dislocation was found after a follow-up period of at least 6 months. The mean acetabular cup abduction and anteversion angles were 37.6° (range 32.5°-42°, SD = 1.91°) and 11.1° (range 8.9°-19.2°, SD = 4.02°), respectively. Functional outcomes evaluated using the Barthel index at 6 months follow-up showed that 86% were excellent (mean 17 of 20) (range 7-20, SD = 3.27). A total of 87% of all patients returned to their pre-injury status. Five patients (10%) died after 6 months of follow-up, and all 5 died within 30 days after surgery. There were no cases of revision surgery at 6 months follow-up. Conclusions: THR with imageless computer navigation can provide promising stable hip replacement in elderly patients with femoral neck fractures without dislocation during short-term follow-up.